Barakat Akinsiku’s views in The God of The Sea on Traditional and Modern Beliefs in Marine Ecosystems: Pandangan Barakat Akinsiku dalam The God of The Sea terhadap Kepercayaan Tradisional dan Modern Pada Ekosistem Laut - Rizki, Geubrina (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2024)
This research aims to describe how African people’s traditional and modern beliefs in marine ecosystems as described by the author in The God of the Sea by Barakat Akinsiku (2021). This research uses ecocritical theory with descriptive-qualitative methods. The results show two differences in overcoming the marine ecological crisis: traditional belief is that they use rituals to stop flood disasters, and obtaining blessings such as the death of a baby whale is considered to fulfill people’s living needs. Furthermore, in modern belief, they use methods that educate the public about waste so that people become aware of the plastic waste that is scattered on the beach and sort out what should be recycled and what should not so that the death of a baby whale on the beach is not a blessing, but instead a disaster, the effects of the marine ecological crisis. Based on these two beliefs, the author wants to provide awareness to African governments, primarily to provide free education to African communities who live on coasts with deficient economic levels so that those who live on coasts understand the dangers of rubbish, which can damage marine ecosystems and can protect marine ecosystems for the common good.